Tracking stolen secrets - Scott, Laura, 1961- (Alaska K-9 unit, 2021)
"Positive that her sister isn't involved in a theft ring as the police believe, State Trooper Helena Maddox and her K-9 partner must find her twin before local cop Everett Brand does. But when the niece Helena didn't know existed is left on Everett's doorstep, they all becom targets. Now, working with Everett is Helena's only option to keep the baby safe and prover her sister's innocense . . ."--Page 4 of cover.